(untitled) (A+BE | Architecture and the Built Environment, 2020)
This PhD thesis examines the editorial policies and publishing history of the American periodical Architectural Record in the quarter century from 1942 to 1967. Operating since 1891, the Architectural Record is the longest-living and most circulated professional magazine of architecture, with a strong and lasting impact on the development of the discipline and the profession in the US and abroad. As an archive of architectural knowledge, its history during the mid-20th century is revealing the paradigm shift that occurred in-between the emergence of Modernism in pre-war Europe and its transition to Post-Modernism in the second half of the 20th c., as a largely American issue. The success and influence of the magazine was due to the resources of its parent corporations, F.W. Dodge and McGraw-Hill, its support and acknowledgement by professional and academic organizations and the connections, commitment and inventiveness of its editors. The editorial campaigns of the magazine trace the struggle for the adaptation of the modern movement in the American context and through that to its subsequent global eminence as “contemporary architecture,” a term popularised by the Record. In the midst of the media revolution, the architectural magazines saw the transformation of the profession to an information-based business, beyond an art and an engineering science. At a time when “architectural composition” was redefined into “architectural design.” Amongst the greater media revolution emerging aggressively in the US, the Architectural Record undertook the task of catering for the needs of the practising architect in the post-industrial, managerial and information age. And while initially the magazines were following the architectural developments, reporting on literal images of architecture, by 1967 its editors were educating, managing, consulting and navigating the profession trough its new markets. This trajectory pinackled in the Record’s editorial campaign for “the image of the architect” that exemplified the phenomenon of how magazines were lobbying for the profession. A phenomenon that is still largely inexplored and that defines 21st architectural practice and design. But more than any theoretical sub-narrative, this thesis is dedicated to the history of the people and events that took place behind the pages of this era-defining magazine through the archives and living records of their time.